Naive idiotype-specific CD4+ T cells and immunosurveillance of B-cell tumors. - Lauritzsen, G F (1994)
The immunosurveillance hypothesis suggests that lymphocytes can recognize tumor-specific antigens expressed by transformed cells and initiate their elimination. Immunosurveillance implies that lymphocytes of naive phenotype can home to a tumor site and become activated by tumor-specific antigens. In this study, we have employed T-cell receptor transgenic mice as a source of naive, tumor-specific T cells. The transgenic, CD4+ T cells recognize a 91- to 101-residue fragment of the lambda 2(315) immunoglobulin light chain presented by I-Ed class II molecules. Such naive, idiotype-specific, CD4+ T cells protected against tumor development of a class II negative plasmacytoma (MOPC315) and a class II positive B lymphoma (F9), which both secrete lambda 2(315) immunoglobulin. Adoptive transfer experiments demonstrated that 2 x 10(6) lymph node cells were sufficient for protection against MOPC315. Depletion of T-cell subsets indicated that transgenic CD4+ cells were indispensable for tumor resistance. However, an additional role of CD8+ T cells is not ruled out. In contrast to the resistance against the secreting MOPC315 and F9 cells, transgenic mice were not protected against B lymphoma cells (F67), which do not secrete lambda 2(315) but express a truncated lambda 2(315) chain intracellularly. The results suggest that lambda 2(315) is processed and presented by host antigen-presenting cells, which in turn activate naive, idiotype-specific T cells.